The Crisis of Judicial Impartiality: A Case Study of Bribery in Ronald Tannur’s Acquittal Verdict - Maria Fitriani Longa Rehing; Maria Selfiani Teci; Maria Felisitas Suan; Victor Sonbay; Dar Padji; Fadil Masud (Jurnal Kewarganegaraan, 2026)
The bribery case involving the acquittal of Ronald Tannur, which implicated three judges of the Surabaya District Court in 2024, stands as one of the most shocking events in the history of the Indonesian judiciary. This case fundamentally undermined the principle of judicial impartiality, a cornerstone of a fair judicial system. This study aims to analyze the crisis of judicial impartiality in this case, the factors leading to bribery practices within the judicial system, as well as its impact on the integrity and public trust in Indonesia’s judicial institutions. The research method employed is normative legal analysis using a legislative, conceptual, and case-based approaches. The research findings indicate that this case reflects systemic failures in judicial oversight, a weak culture of judicial integrity, and the ineffectiveness of ethical and criminal sanction mechanisms for corrupt judges. This crisis threatens the fundamental principles of the rule of law and hinders the realization of substantive justice. Comprehensive structural reforms are needed, including strengthening external oversight, ensuring transparency in judicial proceedings, and reforming the judge recruitment and promotion system based on integrity.